(untitled) (Research, Society and Development, 2022)
COVID-19 generated a serious global health crisis, causing thousands of deaths, suffering for families, and various sequelae in survivors, in addition to the adaptation of individuals to the new lifestyle, and consequently, an economic crisis. With this, face-to-face activities had to, in part, reorganize themselves to the distance modality, requiring people to adapt. Thus, nursing students were subjected to rapid changes, from suspension of classes to the emergence of remote teaching, which may have triggered adaptation difficulties and problems related to mental health. In view of this, this study aims to analyze, in the scientific production, aspects about the mental health of nursing students during the COVID-19 pandemic. This is an integrative literature review, carried out between May and June 2021 with the descriptors: mental health, coronavirus infections, and students. Twelve articles were selected and categorized according to textual analysis. To compose the discussion of the findings, the studies were grouped into 2 categories: 1- Psychological consequences of COVID-19 in nursing students; 2- Interferences, learning, and career of nursing students in the COVID-19 pandemic. It was identified that the pandemic was a factor that caused the development or worsening of mental disorders in nursing students. It was possible to trace and affirm that COVID-19, within all the physiological problems, brought harm such as anxiety, fear, stress and depression, caused by factors such as lack of knowledge associated with a new disease, excessive demands from teachers, fear of acquiring the infection and infecting someone in the family, among others.